A Completeness Framework for Critical Success Factors of ERP Implementation Projects: A Stakeholders Perspective - Gupta, Rekha; Naqvi, S. Kazim (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The complex and integrated nature of Enterprise Resourse Planning (ERP) system is often coupled with time constraints and substantial financial commitments that inevitably make its implementation to be a highly risky undertaking . Reviews of the existing literature on the subject suggest that Critical Success Factors (CSFs) have been studied by researchers for risk aversion in ERP implementations. The review studies have often provided different listing of CSFs as per their research settings and scope. ERP projects necessitate organization wide transformation making stakeholders involvement and participation crucial for the success guarantee of the ERP project. Critical Success Factors related to stakeholders are often found in the understated position in spite of the prime contribution and difference they make to ERP implementation success story. The paper focusses on importance of identifying stakeholders CSFs for studying, monitoring and controlling purposes. It further attempts to provide a consolidated list of stakeholders CSFs along with proper categorization.